2014
DOI: 10.1080/00028487.2014.935477
|View full text |Cite
|
Sign up to set email alerts
|

Genetic History of Walleyes Spawning in Lake Erie's Cattaraugus Creek: a Comparison of Pre‐ and Poststocking

Abstract: Fish stocking (artificial supplementation)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…By using microhaplotype genotypes at 8,482 loci, we were able to accurately (> 95%) assign fish of unknown origin to one of three reporting groups of walleye spawning stocks in Lake Erie. Our high assignment accuracy is an improvement relative to previous attempts at differentiating Lake Erie stocks of walleye using microsatellite loci (Stepien et al 2012; Brenden et al 2015) or mitochondrial haplotypes (Stepien and Faber 1998; Gatt et al 2004; Haponski et al 2014). Unlike our approach, which aggregated spawning stocks with low genetic differentiation, these earlier studies treated each spawning stock independently (Strange and Stepien 2007; Stepien et al 2012), and often included only a subset of known stocks within a given basin (Brenden et al 2015; Chen et al 2019).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…By using microhaplotype genotypes at 8,482 loci, we were able to accurately (> 95%) assign fish of unknown origin to one of three reporting groups of walleye spawning stocks in Lake Erie. Our high assignment accuracy is an improvement relative to previous attempts at differentiating Lake Erie stocks of walleye using microsatellite loci (Stepien et al 2012; Brenden et al 2015) or mitochondrial haplotypes (Stepien and Faber 1998; Gatt et al 2004; Haponski et al 2014). Unlike our approach, which aggregated spawning stocks with low genetic differentiation, these earlier studies treated each spawning stock independently (Strange and Stepien 2007; Stepien et al 2012), and often included only a subset of known stocks within a given basin (Brenden et al 2015; Chen et al 2019).…”
Section: Discussionmentioning
confidence: 80%
“…By using microhaplotype genotypes at 8,482 loci, we were able to accurately (> 95%) assign fish of unknown origin to one of three reporting groups of walleye spawning stocks in Lake Erie. Our high assignment accuracy is an improvement relative to previous attempts at differentiating Lake Erie stocks of walleye using microsatellite loci (Stepien et al 2012;Brenden et al 2015) or mitochondrial haplotypes (Stepien and Faber 1998;Gatt et al 2004;Haponski et al 2014).…”
Section: Population Structure and Reassignment Accuracymentioning
confidence: 80%
“…Although our Rapture panel could not reliably discern individual spawning stocks within each basin, we were able to use it to discriminate among three reporting groups (i.e., west/central basin, east basin, and Ontario Grand River) with high reassignment accuracy (93%). Previous attempts at differentiating Lake Erie stocks of walleye using microsatellite loci (Brenden et al, 2015; Stepien et al, 2012) or mitochondrial DNA (mtDNA) haplotypes (Gatt et al, 2004; Haponski et al, 2014; Stepien & Faber, 1998) similarly identified genetic differences between basins, but also could not consistently or reliably assign individuals to independent stocks (20%–87% assignment accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…To establish whether samples represented true populations and statistical assumptions were met, lsat loci were tested for conformance to Hardy-Weinberg equilibrium (HWE) and linkage disequilibrium (LD) assumptions, as well as possible scoring errors, null alleles and large allele dropout following our laboratory protocols (see Haponski et al 2014). LOSITAN (Antao et al 2008) and BAYESCAN (Foll & Gaggiotti 2008) evaluated whether loci conformed to expectations of neutrality or were under possible selection.…”
Section: Genetic Data Analysesmentioning
confidence: 99%